Hubungan Profil Lipid dan Kejadian Migren pada Karyawan di Jakarta - Satyasari, Daniella; Larasari, Andira; Faradilla, Meutia Atika; Anastasya, Karina Shasri (Bioscientist : Jurnal Ilmiah Biologi, 2025)
One of the risk factor for migraines is an elevated lipid profile. The most significant of the primary lipoproteins that causes atherosclerosis and readily binds to blood vessel walls is LDL. Because lipoprotein A (Lp(a)) levels have an atherogenic ApoA structure, increasing oxidative stress and fat oxidation can lead to endogenous vascular injury. Cross-sectional design was used to perform this study from October 2023 to June 2024 in Universitas Trisakti, Faculty of Medicine. The purpose of this study is to evaluate the association between the lipid level and the incidence of migraines among employees in Jakarta. The target population consists of Jakarta's private employees. With a total sample size of 66 employees that meet the inclusion and exclusion criteria, the study sample will be drawn using the sequential sampling method. The study's findings highlighted that high LDL (p=0.002) and total cholesterol (p=0.0001) had a significant relationship with migraines, whereas HDL, triglycerides, and Lp(a) had an insignificant link with the incidence of migraine (p>0.05). The study concluded that LDL is a powerful predictor of migraine occurrence and has a significant association with migraine.